Investigation of insulation characteristics of gfrp crossarm subjected to lightning transient - Abd Rahman M.S.; Ab Kadir M.Z.A.; Abd Rahman M.S.; Osman M.; Mohd Nor S.F.; Zainuddin N.M. (MDPI AG, 2023)
Fiber reinforced plastics; Glass industry; Insulation; Lightning; Dry and wet conditions; Electrical applications; Glass fiber reinforced polymer; High performance composites; Insulation characteristics; Material technologies; Non-uniform distribution; Simulation approach; Transients